Transcriptional and posttranscriptional regulation of the adaptor/scaffold protein gene ITSN1 - Kropyvko, S.V.; Gubar, O.S.; Gryaznova, T.A.; Morderer, D.Ye.; Gerasymchuk, D.O.; Syvak, L.A.; Grabovoy, A.N.; Rynditch, A.V. (Вiopolymers and Cell, 2016)
ITSN1 adaptor/scaffold protein takes part in a variety of physiological and pathological cellular processes. It has a complex expression regulation and many protein partners. Aim. Characterization of the ITSN1 functioning and expression control is important for understanding its role in cell. Methods. Bioinformatic analysis, semi-quantitative expression analysis by RT-PCR, immunoprecipitation. Results. We have described and analyzed the ITSN1 promoter regions, detected ITSN1 alternatively spliced isoforms at mRNA and protein levels in different cancer specimens. By means of different bioinformatic servers, we have identified the sites for miRNA binding and analyzed the sites for serine, threonine and tyrosine phosphorylation of the ITSN1 protein. Conclusions. We have obtained new data on the ITSN1 expression in pathology. We have also shown the possibility of ITSN1 expression regulation by miRNA and phosphorylation of serine, threonine and tyrosine. ITSN1 – адаптерний/скафолдний білок який приймає участь у різноманітних фізіологічних та патологічних клітинних процесах. Він має складну регуляцію експресії та багаточисельні білки партнери. Мета. Характеристика функціонування та регуляції експресії ITSN1 має важливе значення для розуміння ролі ITSN1 в житті клітини. Методи. Біоінформатичний аналіз, напівкількісний аналіз експресії за допомогою ЗТ-ПЛР, іммунопреципітація. Результати. Описано та проаналізовано промоторні регіони ITSN1, детектовано альтернативно сплайсовані ізоформи ITSN1 на рівні мРНК та білка в різних зразках раку. За допомогою різноманітних біоінформатичних серверів виявлено сайти зв’язування з мікроРНК, проаналізовано сайти серин-, треонін- та тирозин-фосфорилювання білка ITSN1. Висновки. Отримано нові дані про експресію ITSN1 при патологіях. Показано можливість регуляції экспресії ITSN1 за допомогою мікроРНК та ролі фосфорилювання серину, треоніну и тирозину в регуляції взаємодії ITSN1 з білками партнерами. ITSN1 – адапторный/скафолдный белок который принимает участие в различных физиологических и патологических клеточных процессах. Он имеет сложное регулирование экспрессии и многочисленные белки партнеры. Цель. Характеристика функционирования и регуляция экспрессии ITSN1 имеет важное значение для понимания роли ITSN1 в жизни клетки. Методы. Биоинформатический анализ, полуколичественный анализ экспрессии с помощью ОТ-ПЦР, иммунопреципитация. Результаты. Описано и проанализировано промоторные области ITSN1, детектировано альтернативно сплайсированные изоформы ITSN1 на уровне мРНК и белка в разных образцах рака. С помощью различных биоинформатических серверов определены сайты связывания с микроРНК, также проанализированы сайты серин-, треонин- и тирозин-фосфорилирования белка ITSN1. Выводы. Получены новые данные о экспрессии ITSN1 при патологиях. Показана возможность регуляции экспрессии ITSN1 с помощью микроРНК и потенциальной роли фосфорилирования серина, треонина и тирозина в регуляции взаимодействия ITSN1 с белками партнерами.